Role of the pharmacist in the management of postmenopausal breast cancer treatment with vasomotor symptoms: A case report - Megan R. Undeberg; Alanda Barash; Kimberly C. McKeirnan (Elsevier, 2023)
This case report describes the pharmacist intervention with a 62-year-old woman who had postmenopausal breast cancer. The patient was experiencing severe vasomotor symptoms from her cancer therapy and wanted to discontinue her treatment despite her risk of cancer returning. Using guidelines for treatment of postmenopausal breast cancer and medication options to mitigate vasomotor symptoms, the pharmacist developed a treatment plan that was acceptable to the patient and approved by the oncologist. Following implementation, the patient was satisfied to experience minimal hot flashes and relayed full compliance with her breast cancer treatment regimen. Pharmacists can play an important role in the management of postmenopausal breast cancer and vasomotor symptoms by providing patient education and recommending medications based on treatment guidelines with consideration to side effects and drug interactions.